2015
DOI: 10.4236/ns.2015.76033
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Intelligence Modalities to Convey Genetic and Genomic Concepts in African American College Biology Students

Abstract: Correct conceptualizations of genetics and genomics are central to understand many aspects of the STEM disciplines as they provide the foundational building blocks for later work in the life sciences. Our study of 435 African American college students investigated the use of culturallyrelevant memes transmitted using multiple intelligence (MI) modalities to convey core genetic and genomic information as an alternative to the traditional teaching approaches. We observed that this approach appears to optimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on the content, Genetics is a relatively complicated subject for students. This difficulty is because Genetics comprises extremely complex instructional materials, abstract concepts, and difficult-to-understand terminology, which results in students occasionally developing misconceptions regarding terms used in Genetics courses (Fauzi & Fariantika, 2018;Fauzi & Ramadani, 2017;Johnson & Jackson, 2015;Murray-Nseula, 2011)with neuropsychological indicators usually being related to subjects with other forms of neurological damage. In this study we assessed the performance of 74 subjects with frontal lobe epilepsy (42 with left, 32 with right frontal epileptic foci.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the content, Genetics is a relatively complicated subject for students. This difficulty is because Genetics comprises extremely complex instructional materials, abstract concepts, and difficult-to-understand terminology, which results in students occasionally developing misconceptions regarding terms used in Genetics courses (Fauzi & Fariantika, 2018;Fauzi & Ramadani, 2017;Johnson & Jackson, 2015;Murray-Nseula, 2011)with neuropsychological indicators usually being related to subjects with other forms of neurological damage. In this study we assessed the performance of 74 subjects with frontal lobe epilepsy (42 with left, 32 with right frontal epileptic foci.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the following studies also show things that are not much different. Genetics is considered difficult for students because the material is abstract, too many terms are difficult to understand, and the material is very complex (Fauzi & Fariantika, 2018;Fauzi & Ramadani, 2017;Johnson & Jackson, 2015;Murray-Nseula, 2011). The complexity inherent in genetics related to genes, DNA, chromosomes, cell division, and inheritance makes it difficult for students to understand (Cimer, 2012;Kibuka-Sebitosi, 2007).…”
Section: / 14mentioning
confidence: 99%
“…The ramifications of inadequate studies of African genomic diversity are not limited to individuals of African descent. In previous studies we have shown that personalized genomic testing can have multiple beneficial educational ramifications for tested individuals (Johnson and Jackson, 2015 ). Even a small amount of data on one African ancestry has been shown to stimulate additional interest in this history and the science behind it.…”
Section: Case 1: Generating Genomic Data Equity In Vulnerable Populatmentioning
confidence: 99%